[factoring completely][section 46]

(1.)  5b2 + 20b - 60             here is the problem

=    5(b2 + 4b - 12)           factor

=    5(b + 6)(b - 2)          factor

(2.)  2x2 + 10x - 28            here is the problem

=    2(x2 + 5x - 14)           factor

=    2(x + 7)(x - 2)          factor

(3.)   4b2 + 26b - 14        here is the problem

=    2(2b2 + 13b - 7)        factor

=    2(2b - 1)(b + 7)        factor

(4.)  12x2 - 10x - 12       here is the problem

=    2(6x2 - 5x - 6)        factor

=    2(3x + 2)(2x - 3)     factor

(5.)  3x2 - 3y2             here is the problem

=    3(x2 - y2)               factor

=     3(x - y)(x + y)        factor

(6.)  24a2 - 54b2           here is the problem

=      6(4a2 - 9b2)        factor

=     6(2a - 3b)(2a + 3b)    factor

(7.)  2y3 - 4y2 - 48y        here is the problem

=    2y(y2 - 2y - 24)       factor

=    2y(y - 6)(y + 4)        factor

(8.)  2m3 - 20m2 + 18m       here is the problem

=    2m(m2 - 10m + 9)          factor

=    2m(m - 9)(m - 1)        factor

(9.)  2a3 - 2a          here is the problem

=     2a(a2 - 1)        factor

=     2a(a - 1)(a + 1)    factor

(10.)  2x2 + 12x - 80      here is the problem

=     2(x2 + 6x - 40)         factor

=     2(x + 10)(x - 4)      factor